Identification of marginal treatment effects using subjective expectations - Joseph Briggs; Andrew Caplin; Søren Leth-Petersen; Christopher Tonetti (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2024)
We develop a method to identify the individual latent propensity to select into treatment and marginal treatment effects. Identification is achieved with survey data on individuals' subjective expectations of their treatment propensity and of their treatmentcontingent outcomes. We use the method to study how child birth affects female labor supply in Denmark. We find limited latent heterogeneity and large short-term effects that vanish by 18 months after birth. We support the validity of the identifying assumptions in this context by using administrative data to show that the average treatment effect on the treated computed using our method and traditional event-study methods are nearly equal. Finally, we study the effects of counterfactual changes to child care cost and quality on female labor supply.
Keywords: C32; C52; C83; J13; J22; 330